Energy aware resource coordination in heterogeneous LTE cellular networks - Abdulkafi A.A.; Kiong T.S.; Koh J.; Chieng D.; Ting A.; Ghaleb A.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Channel coding; Energy efficiency; Frequency bands; Heterogeneous networks; Mobile telecommunication systems; Power management; Power management (telecommunication); Wireless networks; Channel bandwidth; Heterogeneous Network (HetNet); Homogeneous network; Modulation and coding schemes; Overall networks; Resource coordinations; Systems parameters; Users' satisfactions; Wireless telecommunication systems